Rasagiline Exerts Neuroprotection towards Oxygen–Glucose-Deprivation/Reoxygenation-Induced GAPDH-Mediated Cell Death by Activating Akt/Nrf2 Signaling - Shimon Lecht; Adi Lahiani; Michal Klazas; Majdi Saleem Naamneh; Limor Rubin; Jiayi Dong; Wenhua Zheng; Philip Lazarovici (Biomedicines, 2024)
Rasagiline (Azilect®) is a selective monoamine oxidase B (MAO-B) inhibitor that provides symptomatic benefits in Parkinson’s disease (PD) treatment and has been found to exert preclinical neuroprotective effects. Here, we investigated the neuroprotective signaling pathways of acute rasagiline treatment for 22 h in PC12 neuronal cultures exposed to oxygen–glucose deprivation (OGD) for 4 h, followed by 18 h of reoxygenation (R), causing 40% aponecrotic cell death. In this study, 3–10 µM rasagiline induced dose-dependent neuroprotection of 20–80%, reduced the production of the neurotoxic reactive oxygen species by 15%, and reduced the nuclear translocation of glyceraldehyde-3-phosphate dehydrogenase (GAPDH) by 75–90%. In addition, 10 µM rasagiline increased protein kinase B (Akt) phosphorylation by 50% and decreased the protein expression of the ischemia-induced α-synuclein protein by 50% in correlation with the neuroprotective effect. Treatment with 1–5 µM rasagiline induced nuclear shuttling of transcription factor Nrf2 by 40–90% and increased the mRNA levels of the antioxidant enzymes heme oxygenase-1, (NAD (P) H- quinone dehydrogenase, and catalase by 1.8–2.0-fold compared to OGD/R insult. These results indicate that rasagiline provides neuroprotection to the ischemic neuronal cultures through the inhibition of α-synuclein and GAPDH-mediated aponecrotic cell death, as well as via mitochondrial protection, by increasing mitochondria-specific antioxidant enzymes through a mechanism involving the Akt/Nrf2 redox-signaling pathway. These findings may be exploited for neuroprotective drug development in PD and stroke therapy.